Fetal echocardiographic predictors of biventricular circulation in hypoplastic left heart complex. (1st September 2021) - Haberer, K.; Fruitman, D.; Power, A.; Hornberger, L. K.; Eckersley, L.
ABSTRACT: Objectives: To determine which echocardiographic features of hypoplastic left heart complex (HLHC) in the fetal period are predictive of biventricular (BV) circulation and to evaluate the long‐term outcome of patients with HLHC, including rates of mortality, reintervention and development of further cardiac disease. Methods: Echocardiograms of fetuses with HLHC obtained at 18–26 weeks and 27–36 weeks' gestation between 2004 and 2017 were included in the analysis. The primary outcome was successful BV circulation (Group 1). Group 2 included patients with single‐ventricle palliation, death or transplant. Univariate analysis was performed on data obtained at 18–26 and 27–36 weeks and multivariate logistic regression was performed on data obtained at 27–36 weeks only. Results: Of the 51 included cases, 44 achieved successful BV circulation (Group 1) and seven did not (Group 2). Right‐to‐left/bidirectional foramen ovale (FO) flow and a higher mitral valve (MV) annulus Z ‐score were associated with successful BV circulation on both univariate and multivariate analysis. Bidirectional or left‐to‐right FO flow, left ventricular length (LVL) Z ‐score of < –2.4 and a MV Z ‐score of < –4.5 correctly predicted 80% of Group 2 cases. Late follow‐up was available for 41 patients. There were two late deaths in Group 2. Thirteen patients in Group 1 required reintervention, 12 developed mitral stenosis and five developed isolated subaortic stenosis. Conclusions: BV circulation is common in fetuses with HLHC. Higher MV annulus and LVL Z ‐scores and right to left direction of FO flow are important predictors of BV circulation. Long‐term sequelae in those with BV circulation may include mitral and subaortic stenosis. © 2020 International Society of Ultrasound in Obstetrics and Gynecology.